Peran Financial Literacy dan Income Terhadap Financial Technology dengan Financial Management Behavior Sebagai Variabel Mediasi - Soleha, Erin; Tan, Emmelia (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The purpose of this study is to find out how the role of Financial Literacy and income in the use of digital wallet financial technology products is mediated by the Financial Management Behavior variable. The data in this study is primary data collected through online questionnaires and additional in-person interviews, secondary data is data from OJK, BI and several scientific articles used as references. The sample in this research was millennial generation and generation Z women in West Java Province. The sample collection technique uses Accidental Sampling. The analysis method uses Structural Equation Modeling (SEM) with SmartPLS software. The results showed that financial literacy on financial management behavior and financial literacy on financial technology did not have a direct effect, followed by financial literacy on financial technology which was mediated by financial management behavior which also did not have an indirect effect. Meanwhile, income on financial management behavior, income on financial technology and financial management behavior on financial technology has a direct influence and income on financial technology mediated by financial management behavior has an indirect effect